2010
DOI: 10.3174/ajnr.a2009
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Risk of Oculomotor Nerve Deficits between Detachable Balloons and Coils in the Treatment of Direct Carotid Cavernous Fistulas

Abstract: BACKGROUND AND PURPOSE:Transarterial balloon embolization used to be the preferred method for treating DCCFs; however, a strayed, overinflated, or migrated balloon may lead to oculomotor palsy. This investigation compared the use of detachable balloons and GDCs, which were previously used only in cases of balloon-technique failure and are now increasingly used as a first-line treatment for DCCFs, in terms of the risk of oculomotor nerve deficit, mortality/morbidity, and initial angiographic results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…Previously in the literature there have been some CCF case reports with cranial nerve palsies 10,11 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously in the literature there have been some CCF case reports with cranial nerve palsies 10,11 .…”
Section: Discussionmentioning
confidence: 99%
“…In their study including 48 patients with direct CCFs who were treated with transarterial balloon detachment technique, Tsai et al reported fi ve patients with oculomotor nerve palsy, four of them with abducens nerve palsy and one with simultaneous third and sixth cranial nerve palsy 11 . Th ey also documented that Guglielmi detachable coils had a lower risk of procedure-related oculomotor nerve defi cit in the treatment of direct CCFs 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Dense packing is mandatory to occlude the fistula, and if not achieved, residual, recurrent fistula or pseudoaneurysm formation (in cases of TCCF; e.g., patient 3 in this series) might occur. 1,8,14,44,45 The principle to be followed during coiling of both TCCFs and DCCFS is the same, which entails coiling to commence at the SOV first because all patients have ophthalmic problems. Missing the foot of SOV inside the CS occluded first might carry the risk of inability to find it later after partial CS packing.…”
Section: Platinum Coilsmentioning
confidence: 99%
“…This is most commonly accomplished by occlusion of the cavernous sinus with detachable coils or other endovascular devices or agents through an endovascular, transvenous approach through the inferior petrosal sinus (Mortazavi et al, ). The use of detachable coils in the treatment of carotid cavernous fistulas is associated with a reduced rate of procedure‐related oculomotor nerve deficits as compared to detachable balloons, probably because there is a risk of direct compression of cranial nerves with balloon overinflation or migration (Tsai et al, ).…”
Section: Oculomotor Nerve (Cn Iii)mentioning
confidence: 99%